2020
DOI: 10.12659/ajcr.925897
|View full text |Cite
|
Sign up to set email alerts
|

Third Cranial Nerve Palsy Presenting with Unilateral Diplopia and Strabismus in a 24-Year-Old Woman with COVID-19

Abstract: Patient: Female, 24-year-old Final Diagnosis: Third cranial nerve palsy in a women presenting COVID-19 Symptoms: Ophthalmoplegia Medication:— Clinical Procedure: — Specialty: Ophthalmology Objective: Rare disease Background: Coronavirus disease (COVID 19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is the causative agent of a serious disease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 15 publications
2
59
0
5
Order By: Relevance
“…He was treated with acetaminophen and the nerve palsy resolved within two weeks. Similarly, Belghmaidi et al (2020) reported a 24-year-old female with left oculomotor cranial nerve palsy. She was treated with chloroquine and azithromycin, the nerve palsy completely resolved within six days.…”
Section: Mechanismmentioning
confidence: 87%
See 1 more Smart Citation
“…He was treated with acetaminophen and the nerve palsy resolved within two weeks. Similarly, Belghmaidi et al (2020) reported a 24-year-old female with left oculomotor cranial nerve palsy. She was treated with chloroquine and azithromycin, the nerve palsy completely resolved within six days.…”
Section: Mechanismmentioning
confidence: 87%
“…Recent reports have described neurological involvement in COVID-19, affecting the central nervous system (CNS), peripheral nervous system (PNS) and muscle, as well as causing olfactory dysfunction (Asadi-Pooya & Simani 2020;Mao et al 2020). Incidences of: Guillain-Barre syndrome, Miller-Fisher syndrome, large vessel stroke and isolated cranial neuropathies have recently been reported in the setting of confirmed SARS-CoV-2 infection (Belghmaidi et al 2020;Ben-David et al 2020;Dinkin et al 2020;Falcone et al 2020;Faucher et al 2020;Gutiérrez-Ortiz et al 2020;Oxley et al 2020;Toscano et al 2020). To date, there are few case reports describing isolated cranial nerve palsies.…”
Section: Introductionmentioning
confidence: 99%
“… Miller Fisher Syndrome (MFS) and cranial nerve palsy MFS with acute onset ataxia, loss of tendon reflexes, and ophthalmoplegia and cases of cranial nerve palsies have been reported in several patients recently diagnosed with COVID-19. [ 59 60 61 62 63 64 ] Patients give history of acute onset of diplopia as the ocular complaint. 6 th nerve was most commonly involved followed by oculomotor nerve [ Fig.…”
Section: Neuro-ophthalmic Manifestations Of Covid-19mentioning
confidence: 99%
“… Retrospective Brazil Camelo-Fiho et al, 2020 [ 100 ] Neuro-ophtalmalogical disorder Using OCT, hyperreflective lesions at the level of ganglion cells and inner plexiform layers were found, especially at the papillomacular bundle of both eyes in 11 adult patients. Case series Brazil Marinho et al, 2020 [ 105 ] Optic neuritis in one of 841 patients Retrospective Spain Romero-Sanchez et al, 2020 [ 71 ••] Ophtalmoparesis from cranial nerve palsy Case report USA Dinkin et al, 2020 [ 106 ] Third cranial nerve palsy Case report Morocco Belghmaidi et al, 2020 [ 107 ] Hearing loss SNHL Case report Thailand Sriwijitalai et al, 2020 [ 109 ] SNHL Case report Egypt Abdel Rhman et al, 2020 [ 110 ] COVID-19 was confirmed 1 out of 5 patients with SNHL. Case series Turkey Kilic et al, 2020 [ 111 ] Complete deafness on the right side and profound SNHL on the left side Case report Germany Degen et al, 2020 [ 112 ] FLAIR , fluid-attenuated inversion recovery; GBS , Guillain-Barré Syndrome; ICA , internal carotid artery; MG , myasthenia gravis; MRC , Medical Research Council; OCT , optical coherence tomography; NMS , neuroleptic malignant syndrome; SNHL , sensorineural hearing loss …”
Section: Guillain-barré Syndrome Spectrumsmentioning
confidence: 99%
“…His symptoms deteriorated with worsening left eyelid ptosis, complete loss of depression, horizontal eye movements on the left, and loss of abduction on the right. Moreover, a 24-year woman in Morocco developed diplopia and strabismus of the left eye 3 days after the onset of COVID-19 symptoms [ 107 ]. She was diagnosed as having an acute painless third partial cranial nerve palsy.…”
Section: Neuro-ophthalmological Disordersmentioning
confidence: 99%